(untitled) (Bangladesh Journal of Agricultural Research, 2026)
Potassium (K) is key element for crop productivity and soil fertility. High demand of crop, K fertilization is ignored as appropriate amount in agriculture. Hence, an experiments was conducted in the research field of Horticulture Research Centre, BARI, Gazipur during Rabi season of 2017-18 and 2018-19 to find out the effective dose of potassium to improve growth, yield and quality of garden pea (Pisum sativum L.). Treatments were T1 = Control, T2 = K 30 kg ha-1, T3= K 40 kg ha-1, T4= K 50 kg ha-1 and T5= K 60 kg ha-1 following Randomized Complete Block Design with three replications. Application of 50 kg ha-1 K produced highest green pod (5352 kg ha-1) and seed yield (1568 kg ha-1), and increased 22.3 and 47.6% higher over K control. The highest amount of vitamin C (42.0 mg/100g) and protein (22.4%) were also noted under application of 50 kg ha-1 but. total K uptake (42.4 kg ha-1) was highest with 60 kg ha-1 K. The highest agronomic efficiency (10.1 kg kg-1), physiological efficiency of K (27.0 kg kg-1), and apparent K recovery efficiency (26.2%) were recorded of 50 kg ha-1 K. The maximum benefit cost ratio 5.67 for green pod and 2.91 for seed yields were registered with 50 kg ha-1 K and also superior based on growth, yield traits, nodulation, nutrient content in garden pea and soil fertility enhancement. Results suggest that application of K 50 kg ha-1 could support to achieve the maximum yield and quality of garden pea in experimental K deficient terrace soil. Bangladesh J. Agril. Res. 48(3): 307-323, September 2023